(untitled) (Bangladesh Journal of Urology, 2020)
Pelvic cyst originated from Mullerian or Wolffian duct are reported frequently but ejaculatory duct cysts are very rare. Here we present a rare case of large ejaculatory duct cyst in a diabetic man. In Bangladesh no such case has yet reported. This will be the first case reported in our country. This man was 48 years old presented with post ejaculatory pain, haematospermia, low ejaculatory volume and infertility. On trans rectal ultrasonogram (TRUS) there was 70ml volume retro prostatic midline cyst was found. MRI pelvis confirms the diagnosis. There are different modalities of treatment ranging from observation to open surgery. We chose to open excision with good post operative outcome. Ejaculatory duct cyst is a rare entity. Malignant transformation also reported in ejaculatory duct cyst. Trans rectal ultra sonogram (TRUS) and MRI of pelvic organs are diagnostic. Treatment depends on size of cyst and fertility. Total excision result in complete recovery from symptoms and disease. Transurethral surgery may conserve natural fertility but persistence in complications. Fertility issue in our case depends on intra-cytoplasmic sperm injection which outcome will be seen in future follow up. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.107-111